A Multimodal Analysis of the Ministry of Health in Indonesia’s Covid-19 Advertisement - Suwandi; Ripi Hamdani Purba (Social Sciences Insights Journal, 2023)
This study looks into the analysis of multimodal in covid-19 advertisements. Multimodal commercials for covid-19 are being analyzed in this study to determine their ideational and linguistic content and to see how these aspects interact. The study used a qualitative approach. The data was obtained from YouTube and then screen shotted to create five pictures. Cheong's study employs Halliday theory to detect language function while identifying visual element usage (GSP). The findings revealed that there are visual and linguistic elements in the covid-19 commercial that symbolize the GSP process. Leads, Display, Primary Announcements, Secondary Announcements, Call and Visit, and Tag are the specific terms. Material Process, Actors, Circumstances, and Goals are the linguistic components of ideational function.